Prenatal Attachment and Related Factors in Adolescent Pregnant Women - İNCEDAL SONKAYA, Zehra; DAĞLAR, Gülseren; ÇAKIR, Demet; TEKELİ TAŞKÖMÜR, Aysun (International Journal of Computational and Experimental Science and Engineering, 2023)
The aim of this study was to determine the level of prenatal attachment and related factors in adolescent pregnant women. The study is cross-sectional descriptive type. The sample consisted of 34 adolescent pregnant women who applied to obstetrics outpatient clinics in a Training and Research Hospital. The data were collected between June 2018-June 2019. The Personal Information Form was collected using the Prenatal Attachment Inventory (PAI), Marriage Life Scale (MLS) and Health Practices in Pregnancy Scale (HPPS). The mean scores obtained from the scales are PAI 38.38±11.47; MLS is 32.74±8.16 and HPPS is 94.93±10.87. A significant negative correlation was found between PAI and HPPS mean score, and a positive and strong relationship between PAI and MLS score mean. While the mean score of PAI and MLS in adolescent pregnants is below the average level, HPPS is above the average. Prenatal attachment level was found to be low in those who are secondary school graduates, married for 2 years, whose first pregnancy and gender of the baby were male, and who evaluated the relationship with their husband at a moderate level. Prenatal attachment increases as satisfaction with marriage increases, while prenatal attachment decreases as health practices during pregnancy increase. Midwives should especially evaluate the prenatal attachment level and related factors of adolescent pregnants, and perform applications to increase prenatal attachment.